Isolation and antimicrobial resistance of vancomycin resistant Enterococcus spp. (VRE) and methicillin-resistant S. aureus (MRSA) on beef and chicken meat, and workers hands from slaughterhouses and retail shops in Turkey - TELLI, N; TELLI, AE; BIÇER, Y; TURKAL, G; UÇAR, G (Journal of the Hellenic Veterinary Medical Society, 2022)
The objectives of this study were to determine the presence and antimicrobial resistance of Methicillin Resistant Staphylococcus aureus (MRSA) and Vancomycin Resistant Enterococci (VRE) on beef and chicken carcasses and meat, and workers hands’ at processing time from a cattle and a poultry slaughterhouse, and beef and chicken meat at retail level. Disk diffusion method was used to determine the antimicrobial resistance profile of the Enterococcus spp. and S. aureus isolates. Minimum Inhibitory Concentration (MIC) values were determined for vancomycin and oxacillin resistance. Finally, conventional PCR was performed to determine the presence of the mecA and vanA resistance genes in isolates classified resistant to oxacillin and vancomycin according to MIC values. S. aureus and Enterococcus faecium isolated from 17 (17%) and eight (8%) samples, respectively. E. faecalis was not detected in any sample. The highest resistance rates were to ampicillin (3/5, 60 %) and penicillin G (5/5, 100 %) in MRSA and tetracycline (4/5, 80 %) in VRE isolates. While the mecA gene was detected in all MRSA isolates, vanA gene was not detected in any of the phenotypically vancomycin resistant E. faecium isolates. The present study provides data for multiple antimicrobial resistance and presence of VRE and MRSA isolated from an ongoing surveillance in humans, livestock and poultry in Turkey.